PAI TEACHER STRATEGIES IN OVERCOMING STUDENT LEARNING DIFFICULTIES - DINDA DWI SAFITRI (Universitas Muhammadiyah Surabaya, 2025)
Learning strategies are important things that cannot be separated in the PAI learning process because the use of appropriate strategies will be able to overcome PAI learning difficulties. The purpose of this study was to determine the learning strategies of PAI teachers in overcoming learning difficulties of seventh grade students at SMP N 1 Sragi. This research is a qualitative research with the type of case study research. Based on the results of the study, it can be concluded that the PAI teacher's strategy in overcoming the learning difficulties of seventh grade students at SMP Negeri 1 Sragi is to approach individually, conduct individual and group guidance.